U60 Undulator: An Insertion Device for the Siam Photon Source - DASRI, Thananchai (Walailak Journal of Science and Technology (WJST), 2011)
Properties of insertion device, undulators, for the synchrotron light source are reviewed. Undulators are magnetic devices installed in the storage ring to improve the properties of the synchrotron light. First, the ideal simulated undulator fields will be discussed. Later the simulated fields produced by a defective undulator will be shown. Last, their effects on the stored electron beam are presented. The U60 undulator of the Siam Photon Source is used as an example.